EDUKASI WARGA RT 1 PERUMAHAN LINGKAR ASRI TERHADAP VARIAN COVID-19: PENCEGAHAN DAN PENANGANANNYA - Annisa, Nurul Hikmah; Thoyibah, Zurriyatun (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Covid-19 is a disease caused by a new type of coronavirus with clinical symptoms of fever, cough, runny nose, fatigue, lethargy, sore throat, and shortness of breath. One of the efforts to control the spread of the Covid 19 virus is to provide education to the public about the new variant of Covid 19, prevention and how to handle it. This education is expected to provide accurate and reliable information to the community and become a supporting factor and motivation for the community to adapt during this pandemic. Based on this, the service team carried out educational activities about the Covid 19 variant and how to prevent and treat it for residents of RT 1 Lingkar Asri Housing which was held from April 5 to April 30, 2021. Educational activities began with providing education about the new variant of Covid 19, the symptoms of which felt when exposed to Covid 19, prevention and how to handle it. Furthermore, education is also given regarding the self-isolation procedure that must be carried out if there are families affected by Covid 19 and the importance of the Covid 19 vaccination. This health education is carried out using posters and leaflets. In addition, a questionnaire was also given to determine the level of knowledge and understanding of the community regarding the Covid 19 variant, prevention and how to handle it. The results of this community service activity are known if there is an increase in knowledge and understanding of the community of RT 01 Lingkar Asri Housing regarding the Covid 19 variant, prevention and how to handle it from 15% to 80%. These educational and outreach activities are simple things that need to be done consistently, in order to build public awareness in maintaining health, adopting a clean and healthy lifestyle, especially during the current pandemic.